Phylogeography of Ophryotrocha labronica (Polychaeta, Dorvilleidae) along the Italian coasts. (22nd September 2014) - Cossu, Piero; Maltagliati, Ferruccio; Pannacciulli, Federica G.; Simonini, Roberto; Massamba‐N'Siala, Gloria; Casu, Marco; Lardicci, Claudio; Prevedelli, Daniela; Castelli, Alberto
Abstract: Species of the genus Ophryotrocha are a well‐studied group of organisms but, despite the relatively large body of biological studies, little is known about their intra‐specific patterns of genetic diversity. In the present study, we analysed the patterns of genetic variation in samples of Ophryotrocha labronica (Polychaeta, Dorvilleidae) collected along the Italian coasts within three regions with different thermal regimes: the Northern Adriatic Sea (NAS), the Ligurian Sea (LS), and the South/Southeast Sicilian Sea (SS). A partial sequence of the cytochrome c oxidase subunit I (COI) gene was used as a genetic marker. An analysis of molecular variance (AMOVA) showed significant genetic differentiation between the NAS and the other regions. Conversely, little or no genetic structuring was found between the LS and the SS or amongst locations within a given region. A Bayesian phylogenetic tree and a median‐joining network provided evidence for the occurrence of two highly divergent genetic lineages characterized by a high average sequence divergence (17.2%, Kimura two‐parameter distance). The spatial patterns of genetic variation found in O. labronica may reflect the signature of past expansion events of the two genetic lineages. Although the high sequence divergence suggested that cryptic speciation within O. labronica may have occurred, other traits such as the absence of reproductive isolation, pattern of phenotypic variation and habitat specificity prompted us to regard the two groups as distinct COI lineages of O. labronica .